From battlefront to homefront: creation of a civilian walking blood bank. Issue Volume 60:Issue S3(2020) (1st June 2020) - Braverman, Maxwell A.; Smith, Alison; Shahan, Charles Patrick; Axtman, Benjamin; Epley, Eric; Hitchman, Scott; Waltman, Elizabeth; Winckler, Christopher; Nicholson, Susannah E.; Eastridge, Brian J.; Stewart, Ronald M.; Jenkins, Donald H.
Abstract : Hemorrhagic shock remains the leading cause of preventable death on the battlefield, despite major advances in trauma care. Early initiation of balanced resuscitation has been shown to decrease mortality in the hemorrhaging patient. To address transfusion limitations in austere environments or in the event of multiple casualties, walking blood banks have been used in the combat setting with great success. Leveraging the success of the region‐wide whole blood program in San Antonio, Texas, we report a novel plan that represents a model response to mass casualty incidents.